Interdisciplinary Collaborations in Schools: Lived Experiences of School-Based Professionals - Karlesia Montague; Christina Barksdale; Crystal Speaks (Teaching and Supervision in Counseling, 2025)
Collaboration is an ethical duty of school-based professionals and essential to addressing student needs and maximizing student success. This phenomenological qualitative research study explored the collaborative experiences between school counselors, school-based mental health counselors (SBMHCs), and school social workers. Through semi-structured interviews, we examined the experiences of 12 practicing school-based professionals. Using interpretative phenomenological analysis (IPA), we identified five group experiential themes: (a) it takes a village, (b) factors that influence collaboration, (c) advantages of teamwork, (d) challenges in collaborating, and (e) recommendations to improve collaborative practices. Implications for graduate training programs and recommendations for future research studies are discussed.
Keywords: collaboration; school counselors; school-based mental health counselors; school social workers; interpretative phenomenological analysis